Expression, purification and characterization of meta-cleavage enzyme CarBaBb froim Novosphiongobium sp. K - Zulkharnain, A.B; Maeda, R.; Omori, T. (Hibiscus Publisher, 2013)
The meta-cleavage enzyme carbabb of carbazole-degrader novosphiongobium sp. Ka1 werecloned, expressed and purified to homogeneity in escherichia coli strain. The enzyme was cloned with 6x histidine residues attached at the c-terminal of large subunit carbb for purification using affinity chromatography methodprior to gel filtration chromatography. The carbabb, a two-subunit meta-cleavage enzyme, approximately 30 kda for carbb dan 10 kda for carba, was found to be α2β2-heterotetrameric (mr 80,000), showed highest activity at ph 8.5 and temperature 30°c. Carbabb showed highest catalytic activity towards 2,3-dihydroxybiphenyl with kcat/km 4.1 m-1s-1, and overall higher catalytic activities towards biphenyl-type substrates in comparison to catechol-type substrates.Based on the similarities, this meta-cleavage enzyme fromnovosphiongobium sp. Ka1 would also be a good candidate for protein crystallization and structural studies apart from carbabb from strain p. Resinovorans strain ca10.